Green Dakwah and Green Fatwa: The Response of the Muslim Community in Indonesia to Forest and Land Fire Disasters - Jubba, Hasse; Wahdini, Muhammad; Sudirman, Sudirman; Akbar Tanjung, Ardi; Ibrahim Mohamed, Adil Hassan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The involvement of the Muslim community and the use of religious narratives in the conservation of the environment are crucial. This aligns with the normative teachings of Islam found in the Qur'an and Hadith, which emphasize the importance of preserving the environment. One significant environmental issue currently affecting Indonesia is the widespread occurrence of forest and land fires, which has global implications. This situation has prompted the Muslim community to take action. Their response is characterized by an environmental movement that includes initiatives such as this research is qualitative in nature and is based on a literature review of normative documents from three Muslim organizations that are the focus of this study: the Indonesian Ulama Council (MUI), Muhammadiyah, and Nahdlatul Ulama (NU). MUI has specifically addressed this issue by issuing the Green Fatwa, as outlined in Fatwa MUI No. 3 of 2016, which declares the burning of forests and land to be Haram (forbidden). Similarly, both Muhammadiyah and NU have responded by promoting environmental stewardship, urging the community to protect forests and land from fire. They have also engaged in direct action by providing assistance to combat the crisis of forest and land fires. Reason: Improved clarity, readability, and technical accuracy while maintaining the original meaning